Either or Both Competition: A "Two-Sided" Theory of Advertising with Overlapping Viewerships - Markus Reisinger; Attila Ambrus; Emilio Calvano (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper develops a fairly general model of platform competition in media markets allowing viewers to use multiple platforms. This leads to a new form of competition between platforms, in which they do not steal viewers from each other, but affect the viewer composition and thereby the resulting value of a viewer for the other platform. We label this form of competition "either or both." A central result is that platform ownership does not affect advertising levels, despite nontrivial strategic interaction between platforms. This result holds for general viewer demand functions and is robust to allowing for viewer fees. We show that the equilibrium advertising level is inefficiently high. We also demonstrate that entry of a platform leads to an increase in the advertising level if viewers' preferences for the platforms are negatively correlated, which contrasts with predictions of standard models with either/or competition. We validate this result in an empirical analysis using panel data for the U.S. cable television industry.
Keywords: L13; M37; L82; 330